The Effect of Self-Care Deficit Nursing Theory Based Practice Training On Nurse and Patient Outcomes in Internal Medicine Clinics - KISKAC, Nese; KIZILCI OZ, Sevgi (MAS Journal of Applied Sciences, 2023)
This study aims to evaluate the effect of the training given to nurses working in internal medicine clinics so that they can practice based on nursing theory of self-care deficit, on nurse and patient outcomes. The research conducted in a quasi-experimental design. The sample of the study consisted of 33 nurses working in internal medicine clinics and 322 patients. Data collection tools applied to nurses and patients before and after the training. After the training given to nurses; it found that the time spent by nurses for patient care increased, their attitude evidence-based practices, patient-centered care competence, counseling skills and job motivation increased significantly (p<.05), awareness of nursing actions that support patients’ individuality and perception of their individuality in their own care significantly increased (p<.05). It can be recommended that nurses working in internal medicine clinics should be taught in the nursing theory of self-care deficiency and support the theory-based study, and that the study should be conducted out in different clinics other than internal medicine clinics.